Molecular dynamics analysis of microstructural deformation mechanisms in single crystal copper undergoing equal channel angular pressing - Ping Yang; Huaming Zhang; Tianxin Luan; Ye Jin (AIP Advances)
This study employs molecular dynamics simulations to analyze the crystal structure, lattice rotation, dislocations, twinning, shear strain, and volumetric strain in three copper workpieces during the equal channel angular pressing (ECAP) process. The workpieces, oriented as [100], [110], and [111], are aligned parallel to the Y-axis in the simulation, corresponding to the extrusion direction. The deformation of the three workpieces is primarily achieved through the interaction between twinning and dislocation slip. The [100] oriented workpiece activated multiple slip systems with high shear factors, leading to intense shear deformation. This caused different regions to experience varying strains, resulting in the most dispersed lattice rotation distribution. The intense deformation also generated the most deformation twins, and the interaction between deformation twins and dislocations was the strongest, further increasing the overall dislocation density, thereby causing the most severe grain fragmentation. The [111] oriented workpiece activated only one slip system, causing minimal shear deformation, fewer dislocation interactions, and uniform deformation. The deformation and grain fragmentation of the [110] oriented workpiece were intermediate between the other two orientations. This research provides theoretical insights for optimizing the ECAP process and enhancing copper performance.